"Why Didn't She Walk Away?" Silence, Complicity, and the Subtle Force of Toxic Femininity. Issue 4 (4th December 2018) - Snider, Naomi
Abstract: This article grapples with a question that, amidst an ever-mounting avalanche of sexual abuse claims, feels almost unspeakable: "Why didn't she walk away?" To ask this question is, it feels, almost tantamount to blaming the victim. But, what if we shift the locus of frustration and wonder if the problem is not the question per se, but the binary distinctions between sexual empowerment and victimhood that effectively silences attempts to narrate experiences that fall between the two? In this article, the author seeks to adjust the framework in a way that allows us to ask the question not as accusation or judgment, but as a matter of curiosity about a woman's experience of sexual consent and coercion and the murky waters between the two. Building on psychoanalytic observations that the quality of relatedness determines what's possible for us to feel and know, the author considers the relational and cultural forces that render some women's experience of desire or violation of that desire, unknowable or unspeakable. The article also examines how toxic notions of femininity, coupled with the rigid binary between sexual empowerment and victimhood, can inhibit the coconstruction of sexual meaning and identity in dialogue. In so doing, this article sheds light on barriers, both internal and external, that can prevent women walking away from sexual encounters they come to regret.